2022
DOI: 10.1002/trc2.12355
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department care transition barriers: A qualitative study of care partners of older adults with cognitive impairment

Abstract: INTRODUCTION After emergency department (ED) discharge, persons living with cognitive impairment (PLWCI) and their care partners are particularly at risk for adverse outcomes. We sought to identify the barriers experienced by care partners of PLWCI during ED discharge care transitions. METHODS We conducted a qualitative study of 25 care partners of PLWCI discharged from four EDs. We used the validated 4AT and care partner‐completed AD8 screening tools, respectively, to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In accordance with the informants worry regarding making incorrect clinical judgements and assessments, previous research has found that dementia indeed is associated with decreased accuracy of the older patient presenting illness, [ 29 ] and that communication barriers pose risks for patients. [ 13 , 15 18 ] Specifically for PLwD, whose ED visits are associated with adverse outcomes including functional decline, hospitalization, and mortality, [ 3 , 10 , 11 , 30 , 31 ] with one of the found reasons for adverse outcomes being communication barriers. [ 11 ] Indeed, PLwD are less likely to comprehend their discharge diagnosis and instructions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In accordance with the informants worry regarding making incorrect clinical judgements and assessments, previous research has found that dementia indeed is associated with decreased accuracy of the older patient presenting illness, [ 29 ] and that communication barriers pose risks for patients. [ 13 , 15 18 ] Specifically for PLwD, whose ED visits are associated with adverse outcomes including functional decline, hospitalization, and mortality, [ 3 , 10 , 11 , 30 , 31 ] with one of the found reasons for adverse outcomes being communication barriers. [ 11 ] Indeed, PLwD are less likely to comprehend their discharge diagnosis and instructions.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 , 15 18 ] Specifically for PLwD, whose ED visits are associated with adverse outcomes including functional decline, hospitalization, and mortality, [ 3 , 10 , 11 , 30 , 31 ] with one of the found reasons for adverse outcomes being communication barriers. [ 11 ] Indeed, PLwD are less likely to comprehend their discharge diagnosis and instructions. [ 29 ] ED visits for PLwD are further associated with higher mortality and higher costs compared to patients without dementia, [ 3 , 32 ] in line with the informants’ experience of PLwD requiring more resources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation